2019
DOI: 10.1016/j.enpol.2019.02.056
|View full text |Cite
|
Sign up to set email alerts
|

The structure of attitudes towards shale gas extraction in the United Kingdom

Abstract: Shale gas extraction is a highly controversial process. Despite significant proven or potential reserves, public reaction to extraction have often been negative. In some cases, this has prevented exploration. In this paper, we investigate the structure of public attitudes to shale gas extraction in the context of the United Kingdom, using a dedicated survey of 4,992 respondents. We find that public attitudes to shale gas extraction have a unidimensional structure, such that all questions about the virtues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…e results have suggested that information has an important role in regulating responses to shale gas. is factor has implications for how governments approach policies related to shale gas extraction [5]. However, they did not study the intelligent evaluation model of pressure relief gas drainage in goaf nor did they study the effect of intelligent evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…e results have suggested that information has an important role in regulating responses to shale gas. is factor has implications for how governments approach policies related to shale gas extraction [5]. However, they did not study the intelligent evaluation model of pressure relief gas drainage in goaf nor did they study the effect of intelligent evaluation.…”
Section: Related Workmentioning
confidence: 99%
“…Howell (2018) found that as self-assessed knowledge about hydraulic fracturing decreased, negative views about the technology increased. Moreover, higher levels of actual knowledge also seem to produce more consistent views about support for hydraulic fracturing (e.g., Andersson-Hudson et al 2019). As a result, knowledge of hydraulic fracturing may influence perceived risks.…”
Section: Methodsmentioning
confidence: 99%
“…2016 Baptie et al (2016) Unconventional Oil and Gas Development -Understanding and Monitoring Induced Seismic Activity.…”
Section: Tfsg (2015)mentioning
confidence: 99%